2021
DOI: 10.1186/s12917-021-02952-4
|View full text |Cite
|
Sign up to set email alerts
|

Angelica polysaccharide attenuates LPS-induced inflammation response of primary dairy cow claw dermal cells via NF-κB and MAPK signaling pathways

Abstract: Background Laminitis, an inflammation of the claw laminae, is one of the major causes of bovine lameness, which can lead to enormous economic losses and animal welfare problems in dairy farms. Angelica polysaccharide (AP) is proved to possess anti-inflammatory properties. But the role of AP on inflammatory response of the claw dermal cells has not been reported. The aim of this study was to investigate the anti-inflammatory effects of AP on lipopolysaccharide (LPS)-induced primary claw dermal c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Bovine laminitis, one of the most costly lameness conditions, is an economic drain on producers [ 26 ]. It is generally accepted that the micro-circulation of a blood disorder within the corium induced by microbiota metabolites, such as LPS, lactate, and histamine, is the main pathogenesis of laminitis [ 10 , 11 , 12 ]. Thus, in the present study, we detected the characteristics of rumen microbiota and the concentration of LPS, lactic acid, and histamine in the plasma from cows from control and laminitis groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine laminitis, one of the most costly lameness conditions, is an economic drain on producers [ 26 ]. It is generally accepted that the micro-circulation of a blood disorder within the corium induced by microbiota metabolites, such as LPS, lactate, and histamine, is the main pathogenesis of laminitis [ 10 , 11 , 12 ]. Thus, in the present study, we detected the characteristics of rumen microbiota and the concentration of LPS, lactic acid, and histamine in the plasma from cows from control and laminitis groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although laminitis has attracted enough attention, its physiopathology remains unelucidated. Currently, it is commonly considered as the result of the interaction of various factors, including breeding conditions and metabolic insults, which increase the accumulation of toxic substances, such as histamine, lactic acid, and lipopolysaccharide (LPS), leading to vascular lesions and degradation of the suspensory apparatus of the third phalanx within the digit [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] Chuanxiong and angelica extracts exert anti-inflammatory effects by hindering inflammatory signaling. [ 28 , 29 ] The active ingredient of Safflower, safflower yellow, has anti-inflammatory, analgesic, and immune regulation functions. [ 30 ] Both clematis chinensis and angelicae pubescentis radix extract exert anti-inflammatory effects by reducing pro-inflammatory cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs, consisting of p38, ERK and JNK, are involved in a cascade regulating NF-κB-mediated transcription of the proinflammatory cytokines, i.e. IL-6, IL-1β and TNF-α, and inflammatory mediators, such as NO, iNOS, COX-2 and prostaglandin E2 [ 24 , 34 , 35 ]. Previous reports indicated that ISL inhibited MAPK activities in human liver cancer and colitis [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%